Effect of high intensity interval training on body composition in women before and after menopause: a meta‐analysis. Issue 9 (21st July 2020) - Dupuit, Marine; Maillard, Florie; Pereira, Bruno; Marquezi, Marcelo Luis; Lancha, Antonio Herbert; Boisseau, Nathalie
Abstract : New Findings: What is the topic of this review? A meta‐analysis of the efficacy of high intensity interval training (HIIT) in reducing weight, total fat mass (FM) and (intra)‐abdominal FM in normal‐weight and overweight/obese women before and after menopause. What advances does it highlight? HIIT programmes in women significantly decrease body weight and total and abdominal FM. Their effects are more evident in pre‐ than in postmenopausal women. Cycling HIIT seems more effective than running, especially in postmenopausal women, and training interventions longer than 8 weeks comprising three sessions a week should be promoted. Abstract: High‐intensity interval training (HIIT) is a stimulating modality for reducing body weight and adipose tissue. The purpose of this meta‐analysis was to assess the efficacy of HIIT in reducing weight, total fat mass (FM) and (intra)‐abdominal FM in normal‐weight and overweight/obese women before and after menopause. A structured electronic search was performed to find all publications relevant to our review. Stratified analyses were made of hormonal status (pre‐ vs . postmenopausal state), weight, HIIT modalities (cycling vs . running), programme duration (< or ≥8 weeks) and the methods used to measure body composition (dual‐energy X‐ray absorptiometry vs . computed tomography, Magnetic Resonance Imaging and others). A total of 38 studies involving 959 subjects were included. Our meta‐analysis showed that overall HIIT programmes significantly decrease weight, total and abdominal FM in women. Both normal weight and overweight/obese women lost total FM after HIIT protocols whereas HIIT was only effective in decreasing abdominal FM in women with excess adiposity. When pre‐ and postmenopausal women were considered separately, the effect of HIIT on weight, total and abdominal FM were only significant before menopause. Cycling HIIT seemed more effective than running, especially in postmenopausal women, and training interventions longer than 8 weeks comprising three sessions were more efficient. HIIT is a successful strategy to lose weight and FM in normal weight and overweight/obese women. However, further studies are still needed to draw meaningful conclusions about the real effectiveness of HIIT protocols in postmenopausal women. Abstract :